Factors influencing live-stream shopping behaviour among Malaysian consumers - Yu, Ting Lin; Osman, Syuhaily; Kai, Wah Cheng; Toong, Hai Sam; Xue, Ruiteng; K Rajanthran, Subashini (Association Res Militaris, 2023)
This research generally examines the driving factors that influencing the live-stream shopping behaviour among Malaysian consumers. There were 200 users from Facebook Livestream Channel chosen in the study by applying the method of simple random sampling. Data were collected through self-administered questionnaires and five-point Likert scale were adopted. The results of this research showed that live-stream shopping behaviour had positive significant relationship with perceived usefulness (r=0.724; p=0.001), perceived ease of use (r=0.559; p=0.001), perceived enjoyment (r=0.663; p=0.001), and perceived interactivity (r- =0.604; p=0.001) among Malaysian Consumers. Perceived usefulness is the most significant factor that contributed to the live-stream shopping behaviour among Malaysian consumers in this study. The regression model which consisting of four factors has contributed about 79.4% according to the result of multiple linear regression. Consumer should adopt the live-stream commerce for online purchasing due to its benefit of usefulness. Moreover, online vendors should promote and create awareness to public about features and benefits as well as encourage consumers to use live-stream commerce during purchasing.